Meta-Analysis Summary of Broiler Chicken Trials with Dietary ActigenTM (2009-2012) - Hooge , Danny M.; Kiers, Alexis; Connolly, Aidan (International Journal of Poultry Science, 2012)
Statistical meta-analyses of results from broiler pen trials and a few field trials published during 2009-2012 using dietary Actigen were conducted. Actigen (Alltech, Inc., Nicholasville, Kentucky, USA) is a second-generation, yeast cell wall product considered to be a "growth permitter" through its roles in immune modulation and improved intestinal health. Parameters evaluated were dietary inclusion rates for Actigen, age of birds, body weight, Feed Conversion Ratio (FCR) or feed/gain ratio (F/G ratio) and mortality %. Eighteen reports were collected allowing 29 comparisons of negative control (nCON) diets and Actigen supplemented diets (200 to 800 g/tonne) fed during the entire trials. Similarly, 15 reports were collected allowing 20 comparisons of positive control (antibiotic supplemented) diets and Actigen supplemented diets (200 to 882 g/tonne). When added to basal diets continuously to an average broiler age of 41.72 days (n = 29), Actigen significantly and beneficially changed body weight by +0.0.80 kg (+3.34%), FCR or F/G ratio by -0.033 (-1.84%) and mortality % by -0.80 (-12.5% relative to nCON). Compared with positive control (antibiotic) results, dietary Actigen fed continuously to an average broiler age of 42.73 days (n = 20) gave results statistically equivalent with those of dietary antibiotics. Comparisons between this present meta-analysis and those done previously on another yeast cell wall compound (Bio-Mos) suggest that the second generation product Actigen may be more effective in terms of growth promotion.